Studi Komparasi Hak Nafkah Anak Diluar Nikah Menurut Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata - Putri, Suci Rocky; Yani, Encep Ahmad (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study discusses the comparative legal protection of the right to support children born out of wedlock according to two legal systems in force in Indonesia, namely the Compilation of Islamic Law (KHI) and the Civil Code (KUHPerdata). Children born out of wedlock often face legal uncertainty, especially regarding the right to recognition of identity and provision of support, which has an impact on their protection and welfare. This study uses a normative legal approach with a comparative method, to analyze the extent to which the two legal systems provide protection for children born out of wedlock that is legal according to state and religious law. The results of the study show that both the KHI and the Civil Code recognize the importance of protecting children's rights, including the right to support. However, there are fundamental differences in the legal construction and implementation of the responsibility for providing support. In the KHI, children born out of wedlock do not have a civil relationship with their biological father, unless legally recognized, so that the provision of support is only borne by the mother or the party who recognizes it. Meanwhile, the Civil Code provides a broader possibility for the recognition and imposition of responsibility on the biological father through the mechanism of legal recognition of children. This difference creates legal dualism and has the potential to cause injustice and discrimination against children. Therefore, this study recommends harmonization between the Islamic legal system and civil law in the context of the right to support children born outside marriage, in order to ensure legal protection that is fair, equal, and oriented towards the best interests of the child.